1992
DOI: 10.1002/ajmg.1320440421
|View full text |Cite
|
Sign up to set email alerts
|

Familial syndrome of endocrine and neuroectodermal abnormalities

Abstract: We report on a previously undescribed combination of endocrine and neuroectodermal abnormalities in four sibs from Burma. These abnormalities include low growth hormone levels in response to provocative stimuli, delayed puberty associated with prepubertal levels of gonadotropins in the males and pubertal levels of gonadotropins in the females, type II diabetes mellitus with elevated insulin levels, mild mental retardation, sensori-neural deafness, and alopecia without pili torti. They also had a characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Woodhouse Sakati syndrome is a rare autosomal recessive disorder. To date about 25 families1–12 have been described (Table 1), mostly from the Middle East (Saudi Arabia, Jordan, Lebanon, Turkey), where consanguinity is not uncommon. Our patients were from a consanguineous family and from that region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woodhouse Sakati syndrome is a rare autosomal recessive disorder. To date about 25 families1–12 have been described (Table 1), mostly from the Middle East (Saudi Arabia, Jordan, Lebanon, Turkey), where consanguinity is not uncommon. Our patients were from a consanguineous family and from that region.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid dysfunction was found present in 30% of cases 1, 11, 12. T‐wave abnormalities may be seen on ECG 2, 7, 12…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both GH and IGF‐1 have independent actions, many of which have become apparent recently following the characterization of clinical syndromes and the development of mouse models. Most IGF‐1 originates from the liver and that body growth is controlled by the concentration of IGF‐I in the blood [Holder et al, 1981; Guler et al, 1988]; Crandall et al 1973 and Oerter et al 1992 have demonstrated subnormal and borderline GH level after provocative tests in some of their cases but IGF‐1 is not mentioned in these studies. A recent study demonstrated that IGF‐1 levels are often normal in patients with total anterior hypopituitarism and the liver‐derived IGF‐1 is the main determinant of serum IGF [Sjögren et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…Hypogonadism is a component of various hereditary disorders such Bardet–Biedl syndrome [Reinfrank and Nichols, 1964], Kallmann [Kallman et al, 1944], and Prader–Willi syndromes [Hall and Smith, 1972], but alopecia, deafness, diabetes mellitus, and white matter disease are not described in these syndromes. Other syndromes have been described in which these manifestations, together with mental retardation and/or electrocardiographic abnormalities, variously accompany hypogonadotropic hypogonadism [Crandall et al, 1973; Salti and Salem, 1979; Woodhouse and Sakati, 1983; Al Awadi et al, 1985; Oerter et al, 1992; Hannig and Tiller, 1995]. Devriendt et al 1996 reported a brother and sister from consanguineous parents in whom an extra‐pyramidal disorder was associated with hypogonadotropic hypogonadism and alopecia but without diabetes mellitus or deafness; brain MRI showed a generalized process affecting white matter [Devriendt et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…They reported on 2 inbred Saudi Arabian families with 7 affected individuals suffering from a combination of hypogonadism, sparse hair, diabetes mellitus, mental retardation, and mild deafness [79] . Subsequently, several other families of different ethnic origins, including a Jordanian family from Kuwait, have been described [79][80][81] . Around 54 cases have been reported in the literature so far.…”
Section: Woodhouse-sakati Syndromementioning
confidence: 99%